Metabolic Regulation of Hippocampal Neuroprogenitor Apoptosis After Irradiation. Issue 3 (19th October 2019) - Li, Yu-Qing; Koritzinsky, Marianne; Wong, C Shun
Abstract: The tumor suppressor p53 is an important regulator of cell fate response after DNA damage. Cell fate response following metabolic stresses has also been linked to p53-dependent pathways. In this study, we asked if 5′-adenosine monophosphate-activated protein kinase (AMPK), the master sensor of cellular energy balance, played a role in p53-dependent apoptosis of neural progenitor cells (NPCs) in the hippocampus after irradiation. Adult mice with targeted disruption of p53 or prkaa2 (gene that encodes AMPKα) in the brain were used to determine the role of p53 and AMPK, respectively, in radiation-induced apoptosis of NPCs in the hippocampus. The p53-dependent apoptosis of NPCs was associated with an increase in phospho-AMPK expression in the dentate gyrus at 8 hours after irradiation. Activation of AMPK was seen in granule neurons and subgranular NPCs. Compared with wildtype mice, apoptosis of NPCs was significantly attenuated in AMPK deficient ( nestinCre: prkaa2 fl / fl ) mice after irradiation. AMPK deficiency did not however alter p53 activation in NPCs after irradiation. We conclude that AMPK may regulate apoptosis of hippocampal NPCs after irradiation. These findings suggest that cellular metabolism may play a role in determining cell fate response such as apoptosis after DNA damage in NPCs.